Finding the five‐year window: A qualitative study examining young women's decision‐making and experience of using tamoxifen to reduce BRCA1/2 breast cancer risk. Issue 2 (11th October 2020) - Forrest, Laura E.; Forbes Shepherd, Rowan; Young, Mary‐Anne; Keogh, Louise A.; James, Paul A.
Abstract: Objective: Tamoxifen has been demonstrated to reduce breast cancer risk in high‐risk, premenopausal women. Yet, very few young women with hereditary breast and ovarian cancer syndrome in Australia use tamoxifen, despite this being a less‐invasive option compared to risk‐reducing mastectomy. This study aims to examine young women's decision‐making about and experience of taking tamoxifen to reduce their breast cancer risk. Methods: Young women with a BRCA1/2 mutation participated in semi‐structured qualitative interviews, recruited mainly from a metropolitan clinical genetics service. Data were analysed using an inductive, team‐based approach to thematic analysis. Results: Forty interviews with women aged 20–40 years with a BRCA1/2 mutation were conducted. Eleven women could not recall discussing tamoxifen with their healthcare provider or were too young to commence cancer risk management. Twenty‐three women chose not to use tamoxifen because it is contraindicated for pregnancy or because it did not offer immediate and great enough risk reduction compared to bilateral risk‐reducing mastectomy. Six women who were definite about not wanting to have children during the following 5‐year period chose to use tamoxifen, and most experienced none or transient side effects. Conclusions: Decision‐making about tamoxifen was nuanced and informed by considerations characteristic of young adulthood, especially childbearing. Therefore, clinical discussions about tamoxifen with young women with a BRCA1/2 mutation must include consideration of their reproductive plans.